The Effect of Using Training Apparatus For Developing The Artistic Performance of Throwing From Standing Position (Te-waza ) In Youth Judo Fighters - Tariq, Uoday; Basim, Hussanein (Journal of Physical Education, 2018)
The Effect of Using Training Apparatus For Developing The Artistic Performance of Throwing From Standing Position (Te-waza ) In Youth Judo Fighters The importance of the study lies in throwing skill from standing position for youth judo players using special exercises and training program designed by the researcher for developing the artistic performance of throwing from standing position (Te-waza ). The problem of the study lies in weakness in performance and throwing from standing position. The researcher aimed at designing a training program for developing the artistic performance of throwing from standing position (Te-waza ). The researcher used the experimental method. The subject were (16) youth sport clubs aged (17 – 20) years old of the season 2017. The athletes were (30) judo players their weight class 55 Kgm. The results showed significant differences in favor of the experimental group after applying the special exercises using the proposed apparatus. There are also significant differences in skill tests thus the researchers recommended using the apparatus in developing the skills understudy.